2009
DOI: 10.3354/meps07819
|View full text |Cite
|
Sign up to set email alerts
|

Mating success and its consequences for population growth in an estuarine copepod

Abstract: We conducted experiments on mating success of the estuarine copepod Eurytemora affinis in the San Francisco Estuary, USA. The experimental approach was to isolate virgin pairs (one male and one female) in containers varying in volume from 0.03 to 32 l for 2, 4, or 8 h. Mating was considered successful if viable eggs were produced by individual females subsequently incubated for up to 5 d. The experimental data were analyzed by fitting a 3-parameter model to the data to determine the volume search rate of males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Recent copepod-population growth models suggest that small population densities (Choi andKimmerer 2008, 2009) and biased sex ratios (Kiørboe 2007(Kiørboe , 2008 decrease copepod mating success and subsequent population growth by reducing mate-encounter rates (Kiørboe and Bagøien 2005;Visser and Kiørboe 2006;Kramer et al 2011). Here, we show in small (20-mL) vessels, where encounter rates are not limiting, that E. herdmani mating success is significantly reduced by the presence of a predator cue.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…Recent copepod-population growth models suggest that small population densities (Choi andKimmerer 2008, 2009) and biased sex ratios (Kiørboe 2007(Kiørboe , 2008 decrease copepod mating success and subsequent population growth by reducing mate-encounter rates (Kiørboe and Bagøien 2005;Visser and Kiørboe 2006;Kramer et al 2011). Here, we show in small (20-mL) vessels, where encounter rates are not limiting, that E. herdmani mating success is significantly reduced by the presence of a predator cue.…”
Section: Discussionsupporting
confidence: 44%
“…Trials were conducted in small volumes (20 mL) to facilitate high encounter rates and because this volume is comparable to volumes that yielded maximum mating success in a previous study on the congeneric Eurytemora affinis (Choi and Kimmerer 2009). A consumptive predator treatment (predator present), nonconsumptive predator treatments (physical predator mimic, chemical predator cue, combined physical + chemical predator cue) and a control (predator absent) were randomly assigned to containers (n 5 30 per treatment) and copepods were randomly assigned to each treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once mature, males were randomly placed individual into 60 × 30 mm Petri dishes filled with ~30 mL of >700 μg C L −1 (food-replete) or ~200 μg C L −1 (food-limited) food solutions (Besiktepe and Dam 2002), or filtered sea water (no-food treatment). Choi and Kimmerer (2009) have shown that this small volume of water does not affect mating in Acartia sp. The food solutions consisted of 0.2-μm filtered sea water to which T. weissflogii and Tetraselmis sp.…”
Section: Methodsmentioning
confidence: 97%